Pemberdayaan Masyarakat Melalui Pelatihan Kewirausahaan Berbasis Produk Lokal di Sukarara - Fikri, Nurul; Wijayanti, Hani (Lembaga Publikasi Ilmiah Nusantara, 2024)
Community empowerment is a strategic approach to improving welfare and independence, especially in rural areas. This community service program focuses on entrepreneurship training based on local products in Sukarara Village, known for its woven crafts. The aim of this activity is to enhance the community's ability to manage local potential into high-value products through training in entrepreneurial skills, product innovation, and marketing strategies. The implementation method includes practical training, interactive discussions, intensive mentoring, and result evaluations. The results show an improvement in participants' knowledge and skills in developing local products, such as ikat weaving and its derivatives, which are competitive in the market. Additionally, this activity motivates the community to be more creative and innovative in utilizing local potential sustainably. The impact of this program includes increased income for participants, strengthened local economies, and heightened awareness of the importance of entrepreneurship based on village flagship products. This program proves that entrepreneurship training based on local products can be an effective solution in supporting community empowerment. This article is expected to serve as a reference for similar activities in other regions with unique local potentials.